Namal Part 1 - "Nimra Ahmad" (Lahore: Ilmo Irfan Publashers, 2021)
Namal is a mystery, thriller, and romance novel by Nemrah Ahmed, praised for its complex, character-driven plot, compelling themes of revenge, justice, and spirituality, and realistic portrayals of its flawed characters. While some readers find the pacing to be slow due to extensive use of flashbacks, many reviews highlight the novel's intricate plotting with no plot holes and the emotional investment it creates. The title refers to Surah Namal (The Ant) from the Quran, which is reflected in the story's themes of perseverance and faith.